Method for measuring thickness of battery pole piece
By using liquid resin glue on the lithium battery electrode sheet to form a resin layer, clamping and cutting the electrode sheet, and combining with the three-dimensional measurement equipment, the high cost, long time and difficulty of the existing measurement methods are solved, and fast and accurate measurement of the electrode sheet thickness and on-site guidance are achieved.
Patent Information
- Application Number
- CN202411701093.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
The existing lithium battery pole thickness measurement methods are costly, long and difficult, and cannot provide timely feedback on site to guide production.
By pouring liquid resin glue into the container, forming a resin layer after curing, the electrode sheet to be measured is sandwiched between the resin layers, and vertically cut and polished until the cut surface is perpendicular to the surface of the electrode sheet, and the thickness of the electrode sheet is measured using a three-dimensional measuring device.
It realizes rapid and accurate measurement of battery pole thickness, reduces cost and time, simplifies the sample preparation process, and provides timely feedback on production site guidance.
Smart Images

Figure CN119533352A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a method for measuring the thickness of a battery electrode. Background Art
[0002] The coating and preparation of positive and negative electrodes in the lithium battery industry is a particularly important link. The coating and rolling thickness directly affects the battery performance; the electrode thickness needs to be monitored during the coating and rolling process. The current production line mainly uses micrometers and online thickness detectors to measure the thickness of the electrode, but both measure the overall thickness of the electrode. The above measurement methods are insufficient for monitoring the single-sided thickness of the electrode. When the overall thickness of the production line remains unchanged, but one side of the foil is thick and the other side is thin, it is impossible to determine the abnormality.
[0003] When unilateral thickness measurement is required, samples need to be taken and sent to a professional testing center for laser cutting and sample preparation. The sample preparation time is 3 to 4 hours per piece, and the sample preparation is difficult. After the sample is successfully prepared, it is measured using an electron scanning microscope. This measurement method is costly, time-consuming, difficult, and cannot provide timely feedback to the on-site production site for guidance. Summary of the invention
[0004] The main purpose of the present application is to provide a method for measuring the thickness of a battery electrode to solve the problems of high cost, long time and difficult sample preparation in the related art measurement methods.
[0005] In order to achieve the above object, according to one aspect of the present application, a method for measuring the thickness of a battery electrode sheet is provided, the method comprising the following steps:
[0006] Step S1: Obtain the battery electrode to be tested;
[0007] Step S2: pouring liquid resin glue into the container for the first time, and forming a first resin layer after curing; placing the battery electrode to be tested parallel to the surface of the first resin layer, pouring liquid resin glue onto the surface of the first resin layer in the container for the second time, and forming a second resin layer after curing, to obtain a resin sample in which the battery electrode to be tested is sandwiched between the first resin layer and the second resin layer, and the three are parallel to each other;
[0008] Step S3: vertically cutting the resin sample including the electrode piece to be tested along a direction perpendicular to the surface of the resin sample to obtain a resin sample to be tested whose cut end includes a cross-sectional end of the electrode piece to be tested;
[0009] Step S4: grinding, polishing and deflection correction are performed on the cut surface end of the resin product to be tested until the error between the actual measured value and the theoretical value of the foil thickness of the electrode piece in the cut surface end is within a preset range, thereby obtaining a standard product to be tested in which the cut surface is perpendicular to the surface of the electrode piece to be tested;
[0010] Step S5: using a measuring device to measure the thickness of the electrode in the standard test product to obtain a measured value.
[0011] Further, in step S4, the error between the actual measured value and the theoretical value of the foil thickness is less than or equal to 5% of the theoretical value.
[0012] Furthermore, the measurement error of the thickness of the battery electrode to be measured is ≤3%.
[0013] Further, in step S5, the measuring device includes a three-dimensional measuring device, which can be an electron scanning microscope.
[0014] Furthermore, the thickness of the lithium battery pole piece is measured including the thickness of the foil in the pole piece, the thickness of a single side of the pole piece and the thickness of the coating.
[0015] Further, in step S4, the grinding includes coarse grinding with a water mill using 800-mesh sandpaper and fine grinding with a water mill using 2000-mesh sandpaper.
[0016] Furthermore, during the fine grinding process, the inclination direction of the cut end of the resin test product is determined by repeatedly comparing the error between the actual measured value and the theoretical value of the foil thickness, and the cut surface of the inclined part is corrected and fine ground until the error between the actual measured value and the theoretical value of the foil thickness of the pole piece at the cut end is within a preset range, thereby obtaining a standard test product.
[0017] Furthermore, in step S2, the container is an open container, the bottom surface of the container has a horizontal plane, and the side surface of the container is perpendicular to the bottom surface.
[0018] Furthermore, the first resin layer has a horizontal surface, the battery electrode to be tested is placed horizontally on the surface of the first resin layer, and then the liquid resin adhesive is poured in for the second time, and the second resin layer formed by curing has a horizontal surface; the first resin layer, the battery electrode to be tested and the second resin layer are parallel to each other in the horizontal direction.
[0019] Furthermore, the amount of the liquid resin material poured in for the first time is 1 / 3 to 2 / 3 of the liquid level of the container.
[0020] Furthermore, in step S2, the liquid resin material becomes a colorless and transparent cured resin after being cured.
[0021] Furthermore, the liquid resin adhesive is obtained by mixing metallographic resin powder and solvent at a volume ratio of (1-3):1 at 20-35°C, and the liquid resin adhesive is cured at 20-35°C.
[0022] Furthermore, in step S1, the battery electrode includes a ternary lithium battery electrode.
[0023] Furthermore, the foil material includes copper foil or aluminum foil.
[0024] Furthermore, the battery electrode to be tested is composed of a foil and an active material coating, and the active material coating is arranged on two surfaces of the foil.
[0025] Furthermore, the solid content of the slurry forming the active material coating is 40% to 75%, and the density of the active material coating is 7 to 12 mg / cm 2 .
[0026] By applying the technical solution of the present application, the provided method for measuring the thickness of a lithium battery pole piece has the advantages of easy operation, simple sample preparation, short test time, and low cost, and in particular has the advantages of very high measurement accuracy. It can also measure the single-sided thickness of the battery pole piece or the coating thickness, and can provide feedback and guidance to the production site in real time. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 The electron microscope image of the thickness of the negative electrode sheet of a lithium battery measured in Example 1 of the present application is shown;
[0029] Figure 2 An electron microscope image of the thickness of the negative electrode sheet of a lithium battery measured in Example 2 of the present application is shown;
[0030] Figure 3 The electron microscope image of the thickness of the positive electrode sheet of a lithium battery measured in Example 3 of the present application is shown;
[0031] Figure 4 The SEM image of the single-side coating thickness of the negative electrode sheet of a lithium battery measured in Comparative Example 1 of the present application is shown;
[0032] Figure 5 The SEM image of the coating thickness on another side of the negative electrode sheet of a lithium battery measured in Comparative Example 1 of the present application is shown;
[0033] Figure 6 The SEM image of the copper foil thickness of the negative electrode sheet of a lithium battery measured in Comparative Example 1 of the present application is shown;
[0034] Figure 7 The electron microscope image of the thickness of the negative electrode sheet of a lithium battery measured in Comparative Example 2 of the present application is shown;
[0035] Figure 8 The electron microscope image of the thickness of the negative electrode sheet of a lithium battery measured in Comparative Example 3 of the present application is shown;
[0036] Fig. 9 An electron microscope image of the thickness of the positive electrode sheet of a lithium battery measured in Comparative Example 4 of the present application is shown.
[0037] The above drawings include the following reference numerals:
[0038] 1-Copper foil; 2-Thickness of pole piece on one side, 3-Pole piece thickness, 4-Coating thickness. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0041] Traditional lithium battery electrode thickness measurement technology is insufficient for monitoring the single-sided thickness of the electrode. When the overall thickness of the production line remains unchanged, but one side of the foil is thicker than the other side, it is impossible to determine the abnormality. When single-sided thickness measurement is required, samples must be taken and sent to a professional testing center for laser cutting and sample preparation, which takes 3 to 4 hours per sample. Sample preparation is difficult, costly, and time-consuming, and there is no timely feedback to provide on-site guidance on production sites.
[0042] Therefore, the present application provides a method for measuring the thickness of a battery electrode sheet, the method comprising the following steps:
[0043] Step S1: Obtain the battery electrode to be tested;
[0044] Step S2: pouring liquid resin glue into the container for the first time, and forming a first resin layer after curing; placing the battery electrode to be tested parallel to the surface of the first resin layer, pouring liquid resin glue onto the surface of the first resin layer in the container for the second time, and forming a second resin layer after curing, to obtain a resin sample in which the battery electrode to be tested is sandwiched between the first resin layer and the second resin layer, and the three are parallel to each other;
[0045] Step S3: vertically cutting the resin sample including the electrode piece to be tested along a direction perpendicular to the surface of the resin sample to obtain a resin sample to be tested whose cut end includes a cross-sectional end of the electrode piece to be tested;
[0046] Step S4: grinding, polishing and deflection correction are performed on the cross-section of the resin product to be tested until the error between the actual measured value and the theoretical value of the foil thickness of the electrode piece in the cross-section is within a preset range, thereby obtaining a standard product to be tested in which the cross-section and the surface of the electrode piece to be tested are perpendicular;
[0047] Step S5: using a measuring device to measure the thickness of the electrode in the standard test product to obtain a measured value.
[0048] In order to improve the measurement accuracy of the electrode thickness and achieve the purpose of measuring the single-sided thickness of the electrode, the present application first fixes the electrode to be measured, and after fixation, prepares a relatively standard sample in both the horizontal and vertical directions; since the electrode is relatively thin, about 100-200 microns, and the material is relatively soft, it is impossible to directly cut or measure the electrode; in order to overcome the problem that the electrode is not easy to measure directly, the present application uses a resin with a certain hardness after curing to tightly clamp the thin and soft electrode between two pieces of resin, which plays a role in fixing the electrode, so that the electrode with the cured resin can be easily operated and measured; in this process, the applicant also found that the clamping method or position of the electrode in the resin is different, and the measurement results are quite different. The measurement results of some positions are relatively accurate, and the measurement results of some positions are quite different. After many explorations and experimental verifications, it is found that the reason is that the position of the electrode in the resin is not horizontal and vertical, and it may be tilted. If the rough cross-section is formed by cutting in this tilted state of the electrode, the errors in the two macro aspects are enough to have a serious impact on the micron-level measurement results, and the measurement results are very inaccurate. Therefore, after various attempts, the applicant discovered that the accuracy of measuring the thickness of the pole piece can be significantly improved by first sealing the pole piece horizontally in the resin and then cutting, grinding and polishing the cut surface. Since the thickness of the pole piece is being measured, the cross-section of the pole piece surface and the pole piece thickness direction needs to be vertical. The method adopted in the present application is to first pour liquid resin glue into a container with a flat bottom surface and wait for it to solidify to form a first resin layer. At this time, the resin layer has a relatively flat surface, and then place the electrode to be tested on the surface of the first resin layer in a manner parallel to the first resin layer. At this time, the surface of the electrode to be tested and the surface of the first resin layer are in a relatively parallel state, and then slowly pour the second part of the liquid resin glue on the upper surface of the electrode to be tested, and pour slowly during the pouring process to avoid the movement of the electrode. At this time, the upper and lower surfaces of the electrode to be tested are fixed flat by the solidified resin by utilizing the gravity of the glue itself and the limitation of the container, so that the electrode is not skewed in the solidified resin and is placed relatively horizontally; the above-mentioned method of first curing a layer of resin, then placing the electrode in parallel, and finally curing a layer of resin can ensure that the electrode to be tested is in a horizontal state in the resin, that is, to ensure that the electrode in the cutting surface has a standard horizontality in the X-axis direction.
[0049] The present application defines that the cross section of the electrode to be tested has a standard state in the horizontal direction of the electrode through the above method, which can further improve the measurement accuracy; and the measurement method of the present application has the advantages of easy operation, simple sample preparation, short test time, and low cost, and can measure the single-sided thickness or coating thickness of the battery electrode, which can provide feedback and guidance to the production site in real time.
[0050] In order to further improve the measurement accuracy of the electrode thickness, after ensuring that the electrode has a relatively standard state in the horizontal direction, the present application found that the electrode section is relatively rough, and there will be errors in the vertical cutting, resulting in the cutting surface not being able to reach the standard verticality in the vertical direction. The conventional method only grinds and polishes the section, which can only eliminate some of the more obvious errors and cannot obtain more accurate measurement values. In addition, human observation alone will lead to certain errors in obtaining the verticality of the electrode section. In order to further improve the measurement accuracy, research is conducted from the direction of improving the verticality of the electrode section, and the thickness of the foil in the electrode is cleverly used as a reference value. Due to the theoretical The thickness is known when the electrode is prepared. If the thickness values measured at multiple locations in the copper foil cross section in the electrode section can be close to the theoretical value, it means that the copper foil thickness measurement accuracy is high. It also means that the verticality of the copper foil cross section is good, which means that the verticality of the coating on both sides of the copper foil is relatively good. At this time, the electrode section with this verticality can be used as the standard state in the vertical direction, that is, the section of the electrode to be tested has standard verticality in the y-axis direction; when the electrode to be tested has relatively standard horizontality and verticality, that is to say, the surface and section of the electrode to be tested are relatively vertical, that is, the resin sample to be tested is a horizontal and vertical standard product, then measuring the electrode thickness can greatly improve its accuracy.
[0051] In order to further strictly require measurement accuracy to meet production requirements with high standards, the present application limits the error between the actual measured value of the foil thickness and its theoretical value to less than or equal to 5% of the theoretical value in step S4, for example, less than 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%.
[0052] In some embodiments, the measurement error of the thickness of the battery electrode to be measured is ≤3%, and the measurement method within this error range can be better applied to the lithium battery electrode thickness measurement technology.
[0053] In some embodiments, in step S5, the measuring device includes a three-dimensional measuring device, preferably an electron scanning microscope; other three-dimensional testing instruments can also be used as long as the thickness of each layer in the pole piece section can be measured and read.
[0054] The grinding process in step S4 of the present application includes rough grinding with a water grinder using 800-grit sandpaper and fine grinding with a water grinder using 2000-grit sandpaper. More appropriate rough grinding and fine grinding can also be used for grinding, the purpose of which is to perform detailed and minute step-by-step processing on the end of the resin section to be measured in order to obtain a measurement section with good verticality, smoothness and flatness.
[0055] In some embodiments, during the fine grinding process, the present application determines the inclination direction of the cut end of the resin test product by repeatedly comparing the error between the actual measured value and the theoretical value of the foil thickness, and corrects and fine-grinds the cut surface of the inclined part until the error between the actual measured value and the theoretical value of the foil thickness of the pole piece in the cut end is within a preset range, thereby obtaining a standard test product; that is, taking several positions on the copper foil cross section for measurement and comparison; for example, taking 3 points on each side of the copper foil cross section, taking 3 points in the middle part, or taking an average of 9 points on the copper foil cross section, etc., so that a more real and accurate comparison result can be obtained, so as to further ensure that the verticality of the pole piece cross section is more standard.
[0056] In some embodiments, in step S2 of the present application, the selected container is an open container, the bottom of the container has a horizontal plane, and the side and bottom of the container are vertical; using a container that meets this requirement first limits the resin and the electrode to be in a horizontal direction in a large direction, which is conducive to subsequent further improvement operations on the horizontality and verticality of the sample.
[0057] In some embodiments, the first resin layer of the present application has a horizontal surface. When this layer of resin still has initial viscosity, the battery electrode to be tested is placed horizontally on the surface of the first resin layer. After the electrode is placed on it, due to its light weight, the viscosity can fix the electrode; then pour the liquid resin adhesive for a second time, and the second resin layer formed by curing has a horizontal surface; the upper and lower interlayer resins can be formulated in the same proportion and have the same hardness. The main purpose is to solidify and clamp the electrode so that it does not move during cutting; the first resin layer, the battery electrode to be tested and the second resin layer are parallel to each other in the horizontal direction; that is, the surface of the first resin layer is flat and has a horizontal surface after curing, which can ensure that the lower surface of the placed electrode is also in a horizontal position, and then ensure that the cured second resin layer is also in a horizontal position. Such operation can ensure the horizontal standardization of the entire resin sample to be tested.
[0058] In some embodiments, the amount of the liquid resin material poured in for the first time is 1 / 3 to 2 / 3 of the liquid level of the container.
[0059] In some embodiments, in step S2, the liquid resin material is cured to form a colorless and transparent cured resin. The transparent and colorless cured resin is selected in the present application because the colorless and transparent resin can be cleaned to clearly see the state of the electrode in the resin, and the electrode can be visually seen and cut vertically during cutting.
[0060] In some embodiments, the liquid resin sizing agent is obtained by mixing a solvent and a metallographic resin powder in a volume ratio of (1 to 3): 1 at 20 to 35°C (normal temperature), and the liquid resin sizing agent is cured at 20 to 35°C; the present application adopts the above-mentioned liquid resin sizing agent, and the resin has better hardness after curing, thereby avoiding errors in the softness and hardness of the material caused by cutting.
[0061] In some embodiments, the thickness of the lithium battery pole piece is measured including the thickness of the foil in the pole piece, the thickness of the pole piece on one side, and the thickness of the coating. The method of the present application can not only directly measure the overall thickness of the pole piece, but also measure the thickness of the pole piece on one side, and even the thickness of the coating, and the measurement results are highly accurate.
[0062] In some embodiments, in step S1, the battery electrode includes a ternary lithium battery electrode; the electrode can be a positive electrode or a negative electrode.
[0063] In some embodiments, the foil includes copper foil or aluminum foil, or other types.
[0064] In some embodiments, the battery electrode to be tested is composed of a foil and an active material coating, and the active material coating is disposed on two surfaces of the foil.
[0065] The measurement method of the present application is tested and verified by examples and comparative examples.
[0066] Example 1
[0067] A method for measuring the thickness of a lithium battery electrode sheet, the method comprising the following steps:
[0068] 1) Prepare the negative electrode sheet of the ternary lithium battery by coating the negative electrode slurry on both sides of the 10 μm thick copper foil. The slurry solid content is 46%, and the single-sided coating surface density is 7.07 mg / cm 2 ; Use a ceramic knife to cut the negative electrode sheet into electrode samples with a size of 10mm*10mm;
[0069] (2) mixing a solvent and epoxy resin powder at a mass ratio of 2:1 at room temperature and stirring uniformly to prepare a colorless and transparent resin, pouring the resin into an open cylindrical rubber mold with a horizontal bottom and vertical sides and a diameter of 30 mm and a height of 15 mm to a 1 / 2 liquid level, and curing for 30 minutes to obtain a first resin layer having a flat and smooth horizontal bottom surface;
[0070] (3) When the first resin layer still has initial viscosity, the sample is placed horizontally on the surface of the first resin layer in the mold, and the pole piece is fixed by the first resin layer and does not move; the pole piece and the first resin layer are basically parallel to each other in the horizontal position, and the newly prepared liquid resin glue is poured into the mold for the second time, and the second resin layer formed by curing has a horizontal surface; the first resin layer, the pole piece of the battery to be tested and the second resin layer are parallel to each other in the horizontal direction;
[0071] (4) After the resin in the mold is completely solidified, take out the solidified resin sample to be tested;
[0072] (5) Use a cutting machine to cut the pole piece embedded in the resin in a direction perpendicular to the surface of the resin sample. The cut surface is the cross-sectional end of the pole piece.
[0073] (6) The cut sample cross section was coarsely ground, finely ground and polished using 180 mesh, 400 mesh, 800 mesh, 1500 mesh and 2000 mesh sandpaper respectively;
[0074] Among them, during the fine grinding process, the inclination direction of the cut surface end of the resin test product is determined by comparing the error between the actual measured value and the theoretical value of the foil thickness for multiple times, and the cut surface of the inclined part is corrected and finely ground until the error between the actual measured value and the theoretical value of the foil thickness of the pole piece in the cut surface end is within a preset range; specifically, an average of 9 points are taken on the copper foil cross section for measurement and comparison (three-dimensional microscope), and the error between the measured value and the theoretical value is 2.6%, that is, a standard test product with a cut surface and a pole piece surface perpendicular to each other is obtained, which has good verticality;
[0075] (7) The electrode thickness is measured by electron scanning microscope. When the copper foil thickness is in the range of 9um to 11um (the standard thickness of copper foil is 10um, and the test error is ±1um), the coating thickness on one side of the electrode is 52um and 53um respectively, and the total thickness is 115um. Figure 1 shown.
[0076] Example 2
[0077] A method for measuring the thickness of a lithium battery electrode sheet, the method comprising the following steps:
[0078] 1) Prepare the negative electrode of the ternary lithium battery by coating the negative electrode slurry on both sides of the 10um thick copper foil. The solid content of the slurry is 46%, and the single-sided coating surface density is 8.84mg / cm 2 ; Use a ceramic knife to cut the negative electrode sheet into electrode samples with a size of 10mm*10mm;
[0079] (2) mixing a solvent and an acrylic ester powder at a volume ratio of 2:1 at room temperature and stirring them uniformly to prepare a colorless transparent resin, pouring the resin into an open rubber mold having a horizontal bottom surface and vertical sides to a 1 / 2 liquid level, and obtaining a first resin layer after curing, wherein the first resin layer has a flat and smooth horizontal bottom surface;
[0080] (3) The sample is placed horizontally on the surface of the first resin layer in the mold, with the electrode and the first resin layer basically parallel to each other in the horizontal position. The newly prepared liquid resin is poured into the mold for the second time to fill the mold. The second resin layer formed by curing has a horizontal surface; the first resin layer, the electrode of the battery to be tested and the second resin layer are parallel to each other in the horizontal direction; they have good horizontality.
[0081] (4) After the resin in the mold is completely solidified, take out the solidified resin sample to be tested;
[0082] (5) Use a cutting machine to cut the pole piece embedded in the resin in a direction perpendicular to the surface of the resin sample. The cut surface is the cross-sectional end of the pole piece.
[0083] (6) The cut sample cross section was coarsely ground, finely ground and polished using 180 mesh, 400 mesh, 800 mesh, 1500 mesh and 2000 mesh sandpaper respectively;
[0084] Among them, during the fine grinding process, the inclination direction of the cut surface end of the resin product to be tested is determined by comparing the error between the actual measured value and the theoretical value of the foil thickness for many times, and the cut surface of the inclined part is corrected and finely ground until the error between the actual measured value and the theoretical value of the foil thickness of the pole piece in the cut surface end is within the preset range, that is, the standard product to be tested is obtained; an average of 9 points are taken on the copper foil cross section for measurement and comparison (three-dimensional microscope), and the error between the measured value and the theoretical value is 4.7%, that is, the standard product to be tested with the cut surface and the pole piece surface perpendicular to each other is obtained, which has good verticality;
[0085] (7) The electrode thickness is measured by electron scanning microscope. When the copper foil thickness is in the range of 9um to 11um (the standard thickness of copper foil is 10um, and the test error is ±1um), the coating thickness on one side of the electrode is 64um and 65um respectively, and the total thickness is 140um. Figure 2 shown.
[0086] Example 3
[0087] A method for measuring the thickness of a lithium battery electrode sheet, the method comprising the following steps:
[0088] 1) Prepare the positive electrode sheet of the ternary lithium battery by coating the positive electrode slurry on both sides of the 20um thick aluminum foil. The solid content of the slurry is 71.15%, and the single-sided coating surface density is 14.35 mg / cm 2; Use a ceramic knife to cut the positive electrode into electrode samples with a size of 10mm*10mm;
[0089] (2) mixing a solvent and epoxy resin powder at a ratio of 2:1 at room temperature and stirring to prepare a colorless transparent resin, pouring the resin into an open rubber mold having a horizontal bottom surface and vertical side surfaces to a 1 / 2 liquid level, and obtaining a first resin layer after curing, wherein the first resin layer has a flat and smooth horizontal bottom surface;
[0090] (3) The sample is placed horizontally on the surface of the first resin layer in the mold, with the electrode and the first resin layer basically parallel to each other in the horizontal position. The newly prepared liquid resin is poured into the mold for the second time to fill the mold. The second resin layer formed by curing has a horizontal surface; the first resin layer, the electrode of the battery to be tested and the second resin layer are parallel to each other in the horizontal direction; they have good horizontality.
[0091] (4) After the resin in the mold is completely solidified, take out the solidified resin sample to be tested;
[0092] (5) Use a cutting machine to cut the pole piece embedded in the resin in a direction perpendicular to the surface of the resin sample. The cut surface is the cross-sectional end of the pole piece.
[0093] (6) The cut sample cross section was coarsely ground, finely ground and polished using 180 mesh, 400 mesh, 800 mesh, 1500 mesh and 2000 mesh sandpaper respectively;
[0094] Among them, during the fine grinding process, the tilt direction of the cut surface end of the resin product to be tested is determined by repeatedly comparing the error between the actual measured value and the theoretical value of the foil thickness, and the cut surface of the inclined part is corrected and finely ground until the error between the actual measured value and the theoretical value of the foil thickness of the pole piece in the cut surface end is within the preset range, that is, the standard product to be tested is obtained; an average of 9 points are taken on the cross section of the aluminum foil for measurement and comparison (three-dimensional microscope), and the error between the measured value and the theoretical value is 2.4%, and the standard product to be tested is obtained, which has good verticality;
[0095] (7) The thickness of the electrode was measured using an electron scanning microscope. When the thickness of the aluminum foil was in the range of 19um to 21um (the standard thickness of the aluminum foil was 20um, and the test error was ±1um), the measured single-side coating thickness of the positive electrode was 41um and 39um, respectively, and the total thickness was 100um. Figure 3 shown.
[0096] Comparative Example 1
[0097] (1) Preparation of negative electrode plates for ternary lithium batteries: negative electrode slurry was coated on both sides of a 10 μm thick copper foil. The slurry had a solid content of 46% and a single-sided coating surface density of 7.07 mg / cm 2 ;
[0098] (2) Send the pole piece sample to the testing agency for laser cutting and sample preparation, and use a scanning electron microscope to measure the pole piece thickness;
[0099] (3) When the copper foil thickness is in the range of 9um to 11um (the standard thickness of the copper foil is 10um, and the test error is ±1um), the measured copper foil thickness is 10.31um, and the coating thickness on one side of the electrode is 51.16um and 50.53um respectively, with a total thickness of 112um. Figure 4 , Figure 5 , Figure 6 shown.
[0100] Comparative Example 2
[0101] A method for measuring the thickness of a lithium battery electrode sheet, the method comprising the following steps:
[0102] 1) Prepare the negative electrode of the ternary lithium battery by coating the negative electrode slurry on both sides of the 10um thick copper foil. The solid content of the slurry is 46%, and the single-sided coating surface density is 7.07mg / cm 2 ; Use a ceramic knife to cut the negative electrode sheet into electrode samples with a size of 10mm*10mm;
[0103] (2) Mix a solvent and epoxy resin powder at a ratio of 2:1 at room temperature and stir evenly to prepare a colorless and transparent liquid resin glue, and pour the liquid resin glue into an open rubber mold.
[0104] (3) Insert the electrode sample vertically into the liquid resin glue. After curing, the electrode sample is clamped inside the resin glue;
[0105] (4) After the resin in the mold is completely solidified, take out the solidified resin sample to be tested;
[0106] (5) Use a cutting machine to cut the pole piece embedded in the resin in a direction perpendicular to the surface of the resin sample. The cut surface is the cross-sectional end of the pole piece.
[0107] (6) The cut sample cross section was coarsely ground, finely ground and polished using 180 mesh, 400 mesh, 800 mesh, 1500 mesh and 2000 mesh sandpaper respectively;
[0108] (7) Due to the placement method in step (3), the electrode is randomly floating in the liquid before the resin solidifies. The surface level of the electrode cannot be guaranteed in the X and Y axis directions during cutting. When the electrode thickness is measured using a microscope, it is found that the electrode cross-section under the electron microscope presents an "S"-shaped arc, the thickness fluctuates greatly, and the thickness difference between adjacent parts is obvious. The measured electrode thickness ranges from 141 to 188 um. This result is not representative. Figure 7 shown.
[0109] Comparative Example 3
[0110] A method for measuring the thickness of a lithium battery electrode sheet, the method comprising the following steps:
[0111] 1) Prepare the negative electrode of the ternary lithium battery by coating the negative electrode slurry on both sides of the 10um thick copper foil. The solid content of the slurry is 46%, and the single-sided coating surface density is 7.07mg / cm 2 ; Use a ceramic knife to cut the negative electrode sheet into electrode samples with a size of 10mm*10mm;
[0112] (2) mixing a solvent and epoxy resin powder at a mass ratio of 2:1 at room temperature and stirring them uniformly to prepare a colorless and transparent liquid resin glue, and pouring the liquid resin glue into an open rubber mold;
[0113] (3) The sample is placed horizontally on the surface of the first resin layer in the mold, with the electrode and the first resin layer basically parallel to each other in the horizontal position. The newly prepared liquid resin is poured into the mold for the second time to fill the mold. The second resin layer formed by curing has a horizontal surface; the first resin layer, the electrode of the battery to be tested and the second resin layer are parallel to each other in the horizontal direction; they have good horizontality.
[0114] (4) After the resin in the mold is completely solidified, take out the solidified resin sample to be tested;
[0115] (5) Use a cutting machine to randomly cut the pole piece embedded in the resin, and the cut surface is the cross-sectional end of the pole piece;
[0116] Because the cutting is not perpendicular to the horizontal plane of the pole piece, the pole piece is subjected to shear forces in different directions during cutting. The junction between the material area and the foil area is damaged to varying degrees due to the influence of the bonding force of the pole piece. The foil is soft and easy to bend and stack.
[0117] (6) The cut sample cross section was coarsely ground, finely ground and polished using 180 mesh, 400 mesh, 800 mesh, 1500 mesh and 2000 mesh sandpaper respectively;
[0118] (7) The thickness of the electrode was measured using a microscope. It was found that the electrode morphology was damaged under the electron microscope. Because the cutting position was not perpendicular to the horizontal plane of the electrode, the cut copper foil was bent and folded, and cracks appeared at the interface between the material area and the copper foil. At this time, the measurement results were not representative. Figure 8 shown.
[0119] Comparative Example 4
[0120] A method for measuring the thickness of a lithium battery electrode sheet, the method comprising the following steps:
[0121] 1) Prepare the positive electrode sheet of the ternary lithium battery by coating the positive electrode slurry on both sides of the 20um thick aluminum foil. The solid content of the slurry is 71.15%, and the single-sided coating surface density is 14.35 mg / cm 2; Use a ceramic knife to cut the positive electrode into electrode samples with a size of 10mm*10mm;
[0122] (2) mixing a solvent and epoxy resin powder at a ratio of 2:1 at room temperature and stirring to prepare a colorless transparent resin, pouring the resin into an open rubber mold having a horizontal bottom surface and vertical side surfaces to a 1 / 2 liquid level, and obtaining a first resin layer after curing, wherein the first resin layer has a flat and smooth horizontal bottom surface;
[0123] (3) The sample is placed horizontally on the surface of the first resin layer in the mold, with the electrode and the first resin layer basically parallel to each other in the horizontal position. The newly prepared liquid resin is poured into the mold for the second time to fill the mold. The second resin layer formed by curing has a horizontal surface; the first resin layer, the electrode of the battery to be tested and the second resin layer are parallel to each other in the horizontal direction; they have good horizontality.
[0124] (4) After the resin in the mold is completely solidified, take out the solidified resin sample to be tested;
[0125] (5) Use a cutting machine to cut the pole piece embedded in the resin in a direction perpendicular to the surface of the resin sample. The cut surface is the cross-sectional end of the pole piece.
[0126] (6) The cut sample sections were coarsely ground with 180-mesh and 400-mesh sandpapers respectively;
[0127] The cut samples were not finely ground and polished with fine sandpaper. Since the pole piece aluminum foil is soft and ductile, the aluminum foil in the pole piece was extended during the rough grinding process, covering the material areas on the left and right sides, resulting in an increase in the width of the foil area and a narrowing of the thickness of the material area.
[0128] (7) The thickness of the electrode was measured using a microscope. The thickness of the aluminum foil was 52um (the standard thickness of the aluminum foil was 20um, and the test error was ±1um). The measured single-sided coating thickness of the positive electrode was 26um and 24um, respectively, and the total thickness was 102um. Since the thickness of the aluminum foil of 52um was not compared with the known foil thickness of 20um, the error was too large, so the result was not representative. Fig. 9 shown.
[0129] By comparing the measurement results of Examples 1 to 3 with the laser measurement results of Comparative Example 1, it can be seen that the measurement error of the present application is 3%, indicating that the measurement method of the present application has high accuracy and can be applied to the detection of the single-sided thickness of the electrode in on-site production. In addition, the methods of Examples 1 to 3 are simple to operate, low in cost, and relatively easy to prepare samples. Although the comparative example uses laser detection to obtain higher accuracy, the sample preparation time is at least 3-4 hours, the cost is high, and it is also impossible to achieve on-site measurement and guide production.
[0130] The pole piece thickness of Examples 1 to 3 was measured by laser, and the results were 112um, 136, and 98um, respectively; while the measurement results of the measurement method of Examples 1 to 3 of the present application were 115um, 140um, and 100um, respectively, with errors of 2.67%, 2.96%, and 2.04%, respectively, all within the preset error of 3%.
[0131] By comparing the measurement results of Implementations 1 to 3 with the measurement method of Comparative Example 2, in Comparative Example 2, the electrode to be tested is directly inserted vertically into the liquid glue, and other subsequent operation steps are similar; although the electrode is inserted vertically into the liquid glue to fix and clamp the electrode using the cured glue, when the electrode is inserted vertically into the unsolidified liquid glue, it cannot be guaranteed that the state of the electrode in the resin after solidification is a standard vertical state, and the electrode cannot be solidified in the resin vertically and without shaking due to its own gravity, buoyancy in the glue and other factors. When the electrode is slightly tilted in the resin, the sample of the resin clamped with the electrode after cutting does not have a relatively standard horizontal state in the horizontal direction, and cannot form a horizontal and vertical state with the cutting surface. Samples in this state will inevitably lead to certain measurement errors when measured.
[0132] Furthermore, in Example 2, the electrode is vertically inserted into the liquid glue and its position is allowed to shake due to factors such as gravity or buoyancy, and its vertical state cannot be fixed, which has increased the measurement error. Then, the cut surface is only subjected to conventional grinding, polishing and other treatments, which can only make the cut surface smooth and flat. Whether every part on the cut surface is flat or even the entire cut surface is very vertical, the processing method of Example 2 cannot achieve the above requirements. The processing method for the verticality of the cut surface in Examples 1 to 3 of the present application is based on the accuracy of the copper foil thickness measurement. A relatively flat, smooth, and vertically good cut surface can be obtained. The thickness is measured after the resin sample has a relatively standard state in both the horizontal and vertical directions, and the result is bound to be more accurate.
[0133] By comparing Examples 1 to 3 and Comparative Examples 3 to 4, Comparative Example 3 did not cut the sample vertically, nor did it use the foil as a standard control. The measured copper foil thickness was significantly different from the standard value, indicating that the method has an error in accurately measuring the thickness of the pole piece. Comparative Example 4 did not use fine sandpaper to grind and polish the standard sample, and the actual value of the copper foil thickness measured was significantly different from the standard value. It is inferred that the final measured pole piece thickness error is relatively large. The above shows that in the entire process from sample preparation to measurement, small errors in details will affect the accuracy of the measurement results.
[0134] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of this application.
[0135] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for measuring the thickness of a battery electrode, characterized in that: The method comprises the following steps: Step S1: Obtain the battery electrode to be tested; Step S2: pouring liquid resin glue into the container for the first time, and forming a first resin layer after curing; placing the battery electrode to be tested parallel to the surface of the first resin layer, pouring the liquid resin glue onto the surface of the first resin layer in the container for the second time, and forming a second resin layer after curing, to obtain a resin sample, in which the battery electrode to be tested is sandwiched between the first resin layer and the second resin layer, and the three are parallel to each other; Step S3: vertically cutting the resin sample along a direction perpendicular to the surface of the resin sample to obtain a resin sample to be tested; Step S4: grinding, polishing, and deflection correction are performed on the cross-section of the resin product to be tested in sequence until the error between the actual measured value and the theoretical value of the foil thickness of the electrode piece in the cross-section is within a preset range, that is, a standard product to be tested is obtained in which the cross-section and the surface of the electrode piece to be tested are perpendicular; Step S5: using a measuring device to measure the thickness of the battery electrode sheet to be tested in the standard test product to obtain a measured value.
2. The method for measuring the thickness of a battery electrode sheet according to claim 1, characterized in that: In step S4, the error between the actual measured value and the theoretical value of the foil thickness is less than or equal to 5% of the theoretical value.
3. The method for measuring the thickness of a battery electrode sheet according to claim 1 or 2, characterized in that: In the step S4, the measurement error of the thickness of the battery electrode sheet to be measured is ≤3%.
4. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 3, characterized in that: In the step S5, the measuring device includes a three-dimensional measuring device; A scanning electron microscope is preferred.
5. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 4, characterized in that: The thickness of the battery electrode to be tested includes the thickness of the foil in the electrode, the thickness of a single side of the electrode and the thickness of the coating.
6. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 5, characterized in that: In the step S4, the grinding includes coarse grinding with a water mill using 800-mesh sandpaper and fine grinding with a water mill using 2000-mesh sandpaper.
7. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 6, characterized in that: In step S2, the container is an open container, the bottom surface of the container has a horizontal surface, and the side surface of the container is perpendicular to the bottom surface.
8. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 7, characterized in that: In the step S2, the first resin layer has a horizontal surface, the battery electrode to be tested is horizontally placed on the surface of the first resin layer, and the liquid resin glue is poured in for the second time, and the second resin layer formed by curing has a horizontal surface; the first resin layer, the battery electrode to be tested and the second resin layer are parallel to each other in the horizontal direction; And / or, the amount of the liquid resin material poured in for the first time is 1 / 3 to 2 / 3 of the liquid level of the container.
9. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 8, characterized in that: In the step S2, the liquid resin material becomes a colorless and transparent cured resin after curing; Preferably, the liquid resin sizing material is obtained by mixing a solvent and metallographic resin powder in a volume ratio of (1-3):1 at 20-35°C, and the liquid resin sizing material is cured at 20-35°C.
10. The method for measuring the thickness of a battery electrode sheet according to any one of claims 1 to 9, characterized in that: In the step S1, the battery electrode to be tested is a ternary lithium battery electrode; And / or, the battery electrode to be tested is composed of a foil and an active material coating, and the active material coating is provided on two surfaces of the foil; Preferably, the foil is copper foil or aluminum foil.
Citation Information
Cited By
Pole piece section and preparation method and analysis method thereof
CN121702821A